Hydrogenation of 9-ethylcarbazole as a prototype of a liquid hydrogen carrier - Eblagon, K; Rentsch, D; Friedrichs, O; Remhof, A; Zuettel, A; Ramirez-Cuesta, A; Tsang, S (2010)
Liquid organic hydrides, e.g. 9-ethylcarbazole, are potentially interesting hydrogen storage materials because of their reversible hydrogen sorption properties. In the present work, hydrogenation reaction of 9-ethylcarbazole in the molten form was investigated over a wide variety of noble metal and nickel supported catalysts. The catalytic activity of 8.2 × 10-6 mol-ethylcarbazole/g of metal/s and selectivity of 98% towards a fully hydrogen loaded product were recorded over 5 wt% ruthenium on alumina which was prepared by mild chemical reduction of ruthenium salt. Using this catalyst the theoretical capacity of hydrogen uptake (5.7 wt%) was obtained and the rate of the reaction and activation energy were estimated. Due to its potential high hydrogen storage capacity, this system could be a promising on-board storage candidate for mobile applications. The structures of reaction products and intermediates were identified using 2D NMR techniques. These structures were also predicted to be thermodynamically stable using density functional theory (DFT), matching well with the experimental observations. © 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.